Soy isoflavone intake and prevalence of depressive symptoms during pregnancy in Japan: baseline data from the Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Okubo, Hitomi; Sasaki, Satoshi; Furukawa, Shinya; Arakawa, Masashi (European journal of nutrition, 2018)
Objective Several observational studies and trials examined the relationship between isoflavones or soybeans and depressive symptoms among peri- and postmenopausal women. We cross-sectionally evaluated the associations between intake of soy products and isoflavones and depressive symptoms during pregnancy in Japan. Methods Study subjects were 1745 pregnant women. Dietary intake during the preceding month was assessed using a self-administered diet history questionnaire. Depressive symptoms were defined by a score of 16 or over in the Center for Epidemiologic Studies Depression Scale. Results Higher intake of total soy products, tofu, tofu products, fermented soybeans, boiled soybeans, miso soup, and isoflavones was independently related to a lower prevalence of depressive symptoms during pregnancy: The adjusted prevalence ratios (95 % confidence intervals, P for trend) between extreme quartiles were 0.63 (0.47–0.85, 0.002), 0.72 (0.54–0.96, 0.007), 0.74 (0.56–0.98, 0.04), 0.57 (0.42–0.76, <0.0001), 0.73 (0.55–0.98, 0.03), 0.65 (0.49–0.87, 0.003), and 0.63 (0.46–0.86, 0.002), respectively. A significant positive exposure–response relationship was found between miso intake and depressive symptoms during pregnancy. No material relationship was observed between soymilk intake and depressive symptoms during pregnancy. Conclusions Our study is the first to show independent inverse relationships between intake of total soy products, tofu, tofu products, fermented soybeans, boiled soybeans, miso soup, and isoflavones and depressive symptoms during pregnancy.